PERAN GURU DALAM MEMBENTUK KARAKTER RELIGIUS SISWA PADA MATA PELAJARAN AKIDAH AKHLAK KELAS III DI MI MUJAHIDIN PALEMBANG - Popiyen Suwatila; Maryamah; Muhammad Afandi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Religious character is an important aspect of education that needs to be instilled from elementary school age. This study aimed to determine the role of the Akidah Akhlak teacher in developing the religious character of third-grade students, describe students’ religious character in Akidah Akhlak learning, and identify supporting and inhibiting factors at MI Mujahidin Palembang. This study employed a qualitative approach with a descriptive design. The subjects were the Akidah Akhlak teacher and third-grade students. Data were collected through observation, interviews, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing. The findings show that the teacher acts as a role model, guide, motivator, evaluator, and instructor. Character formation is carried out through habituation of praying, greeting, reading the Qur’an, worship, and practicing politeness, honesty, discipline, care, and responsibility. Students’ religious character has begun to develop, although its application is not yet fully consistent. Supporting factors include students’ awareness, teacher role modeling, adequate facilities, and parental support. Inhibiting factors include low self-awareness, peer environment, limited parental support, and lack of consistent role models. Religious character formation therefore requires cooperation among teachers, schools, families, and the surrounding environment.